(untitled) (Herald of the National Children’s Medical Center, 2025)
Ozaki’s operation is a high-tech method of reconstructing the aortic valve using an autopericardium formed directly during surgery. The method avoids lifelong use of anticoagulants and has demonstrated high efficacy in children with congenital heart defects (CHD) and degenerative changes of the aortic valve. Anesthetic support during this operation requires an integrated approach and mandatory use of intraoperative transesophageal echocardiographic (TP ECHOCG) monitoring.